Experimental Determination on Shale Gas Loss During the Coring Process in Eastern Sichuan Basin - He, Junbo; Tang, Jiren; Zhang, Jing; Ling, Yuanfei; Jin, Dongxu (Frontiers in Energy Research, 2020)
Shale gas loss by leakage directly affects the accurate measurement of shale gas content during drilling and coring. To accurately calculate shale gas loss, in combination with the actual situation of the shale coring, considering the influence factors of the main occurrence state of shale gas (free state and adsorption state), by means of treating the three stages of the shale well core removal, ground exposure, and water bath heating and desorption as a process of desorption that changes with confining pressure, an indoor shale gas loss simulation experiment method was independently designed to determine shale gas loss. Two sets of samples with large differences in physical properties in eastern Sichuan were selected for the shale gas loss simulation experiment. We proposed to use the error reduction rate of shale gas loss (the percentage of the difference between the shale gas loss obtained by the simulation experiment method and the rate obtained by the improved USBM method and curve fitting method and the amount of gas loss of core injected) to verify the accuracy of the simulation experiment method. The results show that compared with the improved USBM method, the average error reduction rate of cores by the experiment method were: 8.64%. Compared with the curve fitting method, the average error reduction rate of cores by the experiment method were 25.11%, which proved that the shale gas loss simulation experiment method had higher accuracy.